Effect of Ho-YAG laser therapy on Complete Blood Count for Lithotripsy (in vitro) - Y. Nazal , Ferial; K. Hamid, Mohammed; R. Akal, Hazim (University of Thi-Qar Journal of Science, 2018)
Background :The purpose of this study is to investigate the in vitro effect of Ho – YAG laser on Complete Blood Picture in blood sample from ureteroscopic lithotripsy ( patients with urinary stones ) . The study is conduct the effect Ho-YAG laser on Complete Blood Count (CBC) was estimated before and after exposure in vitro . The study was conducted on Complete Blood Picture , the taken number of (10) parameters was estimated before and after exposure . Result showed that there was a significant decreased in the percentage of Lymphocyte , PLT , HCT , RBC , HBG , MCHC , after exposure to 2100 nm (Ho-YAG ) laser . It is found that (Ho-YAG ) laser increase some parameters of WBCs , MCV , MONO and MCH and after exposure.